Hubungan Penerapan Ice Breaking dan Motivasi Belajar Siswa Kelas VIII Pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 09 Purwokerto - Fauziah1, Delinda; Muhdi, Ali (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research was conducted based on the low learning motivation of students in class VIII SMP Negeri 9 Purwokerto. Researchers chose ice breaking to overcome the low motivation of students, besides that ice breaking is also used to break the ice, confusion, boredom and saturation of the atmosphere so that it becomes melting and the atmosphere can return to its original state (more conducive). then it is likely that students return to a better condition (enthusiasm, motivation, passion for learning, boredom and so on). The purpose of this study is to analyze whether there is a relationship between ice breaking and motivation. Based on the problems stated earlier and the objectives to be achieved, this research is a quantitative research with experimental design with pretest and posttest research form. The population of this study was all VIII grade students of SMP Negeri 09 Purwokerto which amounted to 292 students, with a research sample of 35 students of class VIII F and 36 students of class VIII G. The data collection method used was a test. The posttest results of the experimental class and control class were converted on a Likert scale. The data analysis techniques used are N-Gain, normality test, and t test. Based on the results of the independent sample t test on the average value of N-Gain of the experimental class and control class, the sig (2-tailed) value obtained is 0.000 which means less than 0.05 which is the limit of significance which shows that H1 is accepted and H0 is rejected. So it can be concluded that there is a significant relationship between creative ice breaking and the learning motivation of class VIII students at SMP Negeri 09 Purwokerto